Cannabis Seeds as a Culinary Ingredient: A Sociological Study of the Acehnese Community - Musanna, Khadijatul; Nabilah, Deva; Suip, Muhammad Nuur Iman bin (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The purpose of this study was to examine marijuana seeds as a flavoring in food among the Acehnese people in the sociological review of Talcott Person. Marijuana based on the Aceh government policy in Aceh Qanun Number 8 of 2018 concerning Drug Abuse Prevention Facilities is a type of intoxicating item and is prohibited for consumption. However, from a cultural perspective, the Acehnese people use marijuana seeds as a flavoring and medicine. Regarding the research method, the author uses qualitative descriptive, while the approach is sociological. The author's primary sources were obtained from the results of observations, interviews and documentation. and secondary data were obtained from related books and journals. The results of the study obtained by the author are the phenomenon of the Acehnese people who use marijuana seeds as a flavoring that is still being implemented today and from sociological studies it has met the standards of Talcott Person's functional theory which is based on actions or cases carried out for a specific purpose. The use of marijuana seeds in cooking aims to make food more delicious and in meat broth cooking makes the meat soft and easy to chew.